Purple Mountain Majesties the story of Katharine Lee Bates and America the beautiful - Younger, Barbara; Schuett, Stacey (New York : Dutton Children's Books, 1998)
A brief biography of the author and college professor whose travels across the United States inspired her to write the poem which became the song "America the Beautiful."
5 - 8 years
Keywords: Bates, Katharine Lee -- 1859-1929 -- Juvenile literature; Women authors, American -- Biography -- Juvenile literature. -- 19th century; Women authors, American -- Biography -- Juvenile literature. -- 20th century; Authors, American; Women -- Biography